Como a heterogeneidade espaço-temporal afeta a diversidade funcional de assembleias de Pelecaniformes e Ciconiiformes em uma planície de inundação. - Almeida, Bia de Arruda (2014)
Floodplains are known to support high biological diversity, and one of the most conspicuous groups in this kind of environment is the waterbird community. Among the waterbirds, Pelecaniformes and Ciconiiformes are important predators of aquatic Vertebrate and Invertebrate, due to their high energy requirements and large populations. Here, we intend to evaluate the Pelecaniformes and Ciconiiformes local assemblies using functional diversity, and through this tool infer about processes structuring assemblies. Thus, in this study we propose the hypothesis that the functional diversity and predominant mechanisms in structuring assemblies differ between environments and along the hydrological cycle. We used bird abundance data collected quarterly over two years in different types of environments of the floodplain of the upper Paraná River. We used three facets of functional diversity (Functional richness, Functional evenness and Functional divergence), and compared the observed values with expected values calculated from randomly generated assemblies to infer about the processes structuring assemblies . The observed functional diversity and the difference between observed and expected FD varied between types of environments and throughout the study period in the floodplain of the upper Paraná River. However, the observed variation agreed only in part with the tested hypothesis, and only in the first year of sampling. A significant increase in the number of species and functional diversity occurred between the flooded and dry periods in the first year of the study, but not in the second, which may have been influenced by small flood pulses occurring during the dry season. The observed values of functional diversity were generally consistent with null expectations, but this pattern may be the result of a complex interaction between different mechanisms structuring assemblies. Comprehending how the functional diversity of waterbirds is affected by the hydrological cycle, and how its dynamics works in the distinct environments of a floodplain is essential to understand how this community behaves in the face of increasingly larger and more frequent changes occurring in the floodplains.